Potato - Colin, J.J. (FAO/IPGRI, 1998)
These guidelines describe technical procedures that minimize the risk of pest introductions with movement of germplasm for research, crop improvement, plant breeding, exploration or conservation. The recommendations in these guidelines are intended for germplasm research, conservation and basic plant breeding programmes. Recommendations for commercial consignments are not the objective of these guidelines. Published in collaboration with the Scottish Agricultural Science Agency (SASA).